Writing Clear Essays - Donald, Robert B. and Morrow, Betty Richmond (Englewood Cliffs Prentice-Hall, Inc., 1992)
This book covers the questions concerning the organization of different types of esays. The author discusses the purpose, thesis statement, outlining, topic sentence, and paragraph of different purposes.
Keywords: Writing